Geochemistry of uranium in Chinese coals and the emission inventory of coal-fired power plants in China. Issue 5 (26th April 2018) - Chen, Jian; Chen, Ping; Yao, Duoxi; Huang, Wenhui; Tang, Shuheng; Wang, Kejian; Liu, Wenzhong; Hu, Youbiao; Li, Qingguang; Wang, Ruwei
ABSTRACT: Uranium, which is of chemotoxic and radiotoxic, is connately present in coals. In view of its dual roles in resource recovery and environmental impact, the geochemistry of uranium in Chinese coals and its atmospheric emission by coal-fired plants in China are discussed in this article. The average uranium concentration of the majority of Chinese coals is 2.43 mg/kg, which is comparable to that of world coals. However, in coals from certain local regions of China, i.e. Yunnan, Guizhou, Guangxi, Xinjiang, Inner Mongolia, and Chongqing Provinces, the uranium is significantly enriched; and even abnormally enriched to form coal-hosted uranium deposits, e.g. coals from the Yili and Tarim Basins of Xinjiang Province, Bangmai Basin of Yunnan Province, and Mabugang Basin of Guangdong Province. Uranium in Chinese coals is associated with organic matter, silicates, pores, pelitic components, phosphate minerals, and uranium minerals. The enrichment of uranium in Chinese coals is attributed to the weathering of source rocks, volcanic ashes, magmatic intrusion, marine water influence, groundwater, hydrothermal fluids, organic matter, palaeoclimate, and the geologic conditions of coal-accumulating basins. Uranium is prior to partition into fly ash. About 62.9 tons of uranium were released into atmosphere from Chinese coal-fired power plants in 2014. Some environmental and human health problems were historically related to uranium in coal worldwide.